2021
DOI: 10.1038/s41598-021-90341-0
|View full text |Cite
|
Sign up to set email alerts
|

White matter hyperintensity in different migraine subtypes

Abstract: The diagnostic value of white matter hyperintensities (WMH) in different types of migraineare unknown. To evaluate the WMH pattern of different subtypes in migraine patients with no vascular risk factors. 92 migraine patients (73 females, mean age 34.6 ± 8.9; 61 episodic migraine, 31 chronic migraine, 36 migraine with aura, 56 migraine without aura) without vascular risk factors underwent brain MRI (3 T). We also included a matched healthy control group with no migraine (n = 24). The prevalence of WMH in diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 63 publications
5
11
1
Order By: Relevance
“…We found that WMHs were significantly higher in number in patients with migraine with aura. Our findings agree with Kurth et al, 2011;Bashir et al, 2013 andKruit et al, 2010 who showed that migraineurs with aura were at increased [11,16,19,25]. Our results are difficult to reconcile with some population-based studies, particularly the study by Gaist et al looking at migraine with aura patients.…”
Section: Discussionsupporting
confidence: 80%
“…We found that WMHs were significantly higher in number in patients with migraine with aura. Our findings agree with Kurth et al, 2011;Bashir et al, 2013 andKruit et al, 2010 who showed that migraineurs with aura were at increased [11,16,19,25]. Our results are difficult to reconcile with some population-based studies, particularly the study by Gaist et al looking at migraine with aura patients.…”
Section: Discussionsupporting
confidence: 80%
“…Prevalence of WMHs was 20% in KD patients, which is four times higher than reported in healthy young adults with a similar age (Hopkins et al, 2006). In contrast, the prevalence of WMH in cases (migraine patients) was comparable to pediatric migraine patients (11 vs. 11%) (Eidlitz-Markus et al, 2013), but lower than reported in young adults with migraine (Dobrynina et al, 2021).…”
Section: Discussionmentioning
confidence: 72%
“…One hypothesis is that vasoactive substances bypass the pulmonary circulation to directly enter the systemic circulation in patients with RLS, inducing migraine attacks and the aura symptoms ( 12 ). While some studies reported an association of RLS with migraine with aura ( 2 ), other studies showed no difference in the prevalence of RLS between migraine subtypes ( 10 , 11 ). Of the types of RLS, a patent foramen ovale (PFO) is the most common and is present in >25% of the healthy population ( 13 ), while other subtypes such as pulmonary arteriovenous malformations are rarer and associated with specific hereditary conditions ( 14 ).…”
Section: Introductionmentioning
confidence: 97%
“…There is recent interest in the relationship between migraine, aura status and RLS ( 1 , 10 , 11 ). One hypothesis is that vasoactive substances bypass the pulmonary circulation to directly enter the systemic circulation in patients with RLS, inducing migraine attacks and the aura symptoms ( 12 ).…”
Section: Introductionmentioning
confidence: 99%